Teaching performance and emotional intelligence in the educational institution ST. George´s College, 2018-2019 - Candela Munayco, Frank Ronny (2020)
The objective of the study was to determine the relationship between secondary level teaching performance management and emotional intelligence in the St. George´s College Educational Institution in the district of Chorrillos, in 2018-2019. It is a research of descriptive correlational type and transversal design; The method used was the hypothetical deductive. The measurement was made in a census sample of 90 teachers. The instruments for the collection of the information were: Framework of the good teaching performance of Enciso and the Inventory of emotional intelligence of BarOn (ICE), adapted by Ugarriza; the same ones that were submitted for validation to the judgment of 5 experts, based on the theoretical framework of the category of “Criteria validity”; and to measure their reliability of both instruments, the Crombach alpha correlation coefficient was applied. The general hypothesis showed a low correlation result of Rho = 0.366, where the management of teacher performance at the secondary level is positively, lowly and significantly related to emotional intelligence. The first, second and third specific hypotheses established a low correlation coefficient of Rho = 0.351, Rho = 0.312 and Rho = 0.386, respectively; and the fourth and fifth specific hypotheses, a very low correlation coefficient of Rho = 0.237 and Rho = 0.245, where the management of teacher performance at the secondary level is significantly related and, positively low, with the components of emotional intelligence : intrapersonal, interpersonal, adaptability, stress management and mood in general.